Evaluating the overall renal outcomes of sodium-glucose cotransporter-2 (SGLT2) inhibitors in patients with chronic kidney disease (CKD) - Min-Jia Cao; Ting-Ting Liang; Li Xu; Fang-Hong Shi (Diabetology & Metabolic Syndrome)
Abstract Background Our meta-analysis fills gaps by assessing sodium-glucose cotransporter-2 (SGLT2) inhibitors’ renal outcomes in chronic kidney disease (CKD) patients including long-term effects and the subgroup analyses of estimated glomerular filtration rate (eGFR) values and follow-up times. Methods The literature search of relevant randomized controlled trials (RCTs) was conducted in Medline, Embase, and the Cochrane Central from the inception to 8 June 2023 on patients with CKD treated with SGLT2 inhibitors. We selected medical subject heading (MeSH) terms and free text terms associated with gliflozin and RCT. We calculated odds ratio (OR) or harzard ratio with 95% confidence intervals (CIs) for composite outcomes and dichotomous data, and weighted mean differences (WMD) for changes in eGFR. Results 16 RCTs enrolling 52,306 patients were in the final population, with 26,910 being treated with SGLT2 inhibitors and 25,396 serving as controls were identified. We found that there was no decline in the rate of change in eGFR after 13 weeks and SGLT2 inhibitors treatment significantly improved the rate of change in eGFR after 64 weeks (64–104 weeks: WMD, 1.024 mL/min/1.73m2/per year, 95% CI 0.643–1.406; 104 weeks: 0.978, 0.163–1.794).SGLT2 inhibitors reduced the risk of acute kidney injury (AKI) (OR 0.836; 95% CI 0.747–0.936; I 2 = 0%), mainly derived from empagliflozin (P = 0.001) and increased the incidence of volume-related adverse events (AEs) by 23%.However, no statically differences were observed in death due to kidney disease (P = 0.182) or events of eGFR < 15 mL/min/1.73 m2 (P = 0.202). Conclusions The results of our meta-analysis showed that after 64 weeks of treatment, SGLT2 inhibitors showed a significant benefit on eGFR rate with no further decline after 13 weeks and the improvement was slighter in lower eGFR values. Additionally, SGLT2 inhibitors reduce AKI when using empagliflozin, while there is an increased risk of volume-related AEs exclusively in stage 2 CKD. Trial registration CRD42023437061.